Investment Climate in Iraq - Reality and Ambition - Iftikhar Mohammed Manahi Al-Rafei (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Investment Environment in the Arab worlds: Presence, Obstacles and Future Prospectus. This study deals with an important topic, which is investment of available various resources for any country and society in order to build strong national economy in facing many challenges and solving many problems which developing countries still suffer from including Arab countries such as unemployment, inflation, poverty and public Debt…….etc. The purpose of this study is to investigate the real investment environment in the IRAQ after 2003. Also the study tries to stand on the real presence, obstacles and trying to find out what the real future and prospectus are to be achieved in light of the challenges of twenty first century.